The Impact of Fluctuations in the Number of Economic Entities in Sectors on Inter-Sectoral Dependencies: Application of Predictions in the Leontief Input-Output Model - Pankowski, Kamil (Wpływ wahań liczby podmiotów gospodarczych w sektorach na zależności międzysektorowe: zastosowanie prognoz w modelu przepływów międzysektorowych Leontiefa, 2025)
The objective of this paper is to examine the impact of fluctuations in the number of economic entities across different sectors on inter-sectoral dependencies. The research is based on data from the Central Statistical Office and the application of the Leontief input-output model. The goal of the study is to recognise dependencies between sectors and determine which sectors are most susceptible to changes in other parts of the economy. In the analysis, advanced analytical tools were used, including the input-output model which allows for a precise assessment of inter-sectoral flows. The results of the research indicate notable differences in the resilience of individual sectors to changes, as well as the presence of potential supply gaps that may arise from a reduction in the number of entities in certain sectors. The conclusions drawn from the analyses can serve as a foundation for managerial decision-making and for developing effective risk management strategies.
Quote as: Pankowski, K. (2025). The Impact of Fluctuations in the Number of Economic Entities in Sectors on Inter-Sectoral Dependencies: Application of Predictions in the Leontief Input-Output Model. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 203-220). Publishing House of Wroclaw University of Economics and Business.
Keywords: fluctuation; Leontief model; inter-sectoral analysis; economic risk; supply gap; prediction; wahania liczby podmiotów gospodarczych; model Leontiefa; analiza międzysektorowa; ryzyko gospodarcze; luka podażowa; prognozowanie